Teachers' Efforts to Improve English Language Skills in 5-6 Year Old Children Through the Montessori Method at KIDEA Kindergarten, Kelapa Gading District, North Jakarta - Marhamah Marhamah; Wening Rahayu; Dini Hidayati; Bayu Andika Prasatyo (Journal of General Education and Humanities, 2026)
Early childhood is a critical period for language development, including English learning. Preliminary observations at KIDEA Kindergarten, Indonesia, showed that children aged 5–6 years were passive, lacked confidence, and had difficulty naming and describing objects in English. Previous studies have not sufficiently explored Montessori-based play materials for English learning in this context. This study aimed to examine the effect of the Montessori method on children's English language skills. This study employed classroom action research consisting of three cycles involving 15 kindergarten children. Data were collected through observation sheets, interviews, and questionnaires, and analyzed using descriptive percentage techniques. The results showed improvement in English language skills from Cycle I (29.0%) to Cycle II (55.0%) and Cycle III (74.8%). Learning participation also reached 77.4% in Cycle III, while student satisfaction increased from 67% to 87%–93%. The findings indicate that the Montessori method supported children's English development through structured play, repeated vocabulary exposure, and teacher scaffolding. In conclusion, Montessori-based learning improved English skills in this context. The study suggests its potential as an alternative approach in early childhood English instruction.